Determinación de la formulación más adecuada de dieta para trucha arco iris (oncorhynchus mykiss) en sus diferentes etapas de desarrollo. - Echevarría Ruiz, Marlon Yordano (2015)
The objective of this research was to determine the most appropriate formulation of diets for rainbow trout (Oncorhynchus mykiss) at different stages of development, this three diets with the use of the Software Alite, one for each phase were formulated taking into account their nutritional requirements; then testing the food formulated for a period of 4 weeks (28 days) feeding trout of the same species and evaluate the biometric growth: Length Standard Single (LSI), Live Weight Single (PVI) Individual Weight Gain (GPI) and Feed Conversion Rate (ICA). After formulated diets by Alite Software, were processed under the quality characteristics of a commercial extruded pellet type, while experimental ponds were adapted into a fish farm located in the town yalen, Pataz - La Libertad, to evaluate each formulation in triplicate for 4 weeks. For formulation I 100 fingerling rainbow trout in each channel was fed 4 times a day with the preparation for the formulation II and III food has had 50 youth and 50 adults, respectively, of the same species per pond, fed 3 times up with that food. It was determined the Formulation I, food for fry, obtained a 84 ± 0.01 ICA smaller and better than the 0.90 recommended for this stage theoretical; formulation II, food for juveniles, likewise shows a better ICA 0.02 ± 0.94 value than the theoretical 1.00 both much better at studies by other authors, while formulation III, adult food, reported a 1.16 ICA ± 0.04, similar to previous studies and fencing theorist 1.00.El this study improved ICA levels in rainbow trout in each of its stages of development showing that the software helps optimize and formulate diets that help accelerate the growth cycle in less time.